Peningkatan Hasil Belajar Matematika Melalui Metode Plantet Question Pada Siswa Sman 3 Parepare - Abdul Rahman (Universitas Pancasakti, 2023)
This research is a class action research (classroom action research) which aims to improve mathematics learning outcomes through the plantet question method in class XF students of SMA Negeri 3 Parepare. The subjects of this study were 14 students of class XF at SMA Negeri 3 Parepare. The research carried out in two cycles. Data collection was carried out by giving cycle I tests then cycle II tests. The collected data were analyzed quantitatively and qualitatively. The results of this study indicate that there is an increase in students' mathematics learning outcomes after learning through the plantet question method. In cycle I, the number of students who completed their studies was 5 students (35.71%) with an average score of 60.71 out of an ideal score of 100 in the low category. While in cycle II the number of students who completed their studies was 14 students (100%) with an average score of 83.14 in the high category. In addition, during the learning process, it shows a change in behavior and better student activity. Meanwhile, the average student activity that was not in accordance with learning decreased from cycle I to cycle II. This is in line with the increasing ability of teachers to manage learning. From the results of this study, it can be concluded that the results of students' mathematics learning through the plantet question method in class XF students of SMA Negeri 3 Parepare increased.